APPLICATION OF EXCLUSIVE BREASTFEEDING TO MOTHERS WITH INVERTED NIPPLES - Seventina Nurul Hidayah; Nora Rahmanindar; Evi Zulfiana (SEAJOM: The Southeast Asia Journal of Midwifery, 2022)
During breastfeeding the mother's reason for not breastfeeding her baby's nipples are difficult to breastfeed because of the anatomical condition of the nipple due to the wrong way of breastfeeding or improper care of the breast. This reason can cause mothers to stress so that the hormone oxytocin does not work and breast milk stored in the breasts causes mothers to switch to using formula milk. This study aims to analyze the factors that influence the application of exclusive breastfeeding in mothers with inverted nipples in Kudaile Village, Tegal Regency. The specific target in this study is that factors are found that influence the application of exclusive breastfeeding so that it can contribute to increasing the scope of exclusive breastfeeding in Kudaile Village. This research uses qualitative methods with an observational design. Data collection was carried out using indeepth interview techniques in accordance with interview and observation guidelines. The results of the interview were recorded and field notes were made. To avoid subjectivity, researchers use the source triangulation technique which is to collect data from different sources (informant families) by the same method (in-depth interviews)